Kontribusi Implementasi Pendidikan Karakter dan Lingkungan Sekolah terhadap Berpikir Kreatif serta Dampaknya pada Kompetensi Kejuruan - Akhmad Fadli; Abdullah Isa (Sekolah Tinggi Agama Islam Taruna Surabaya, 2021)
The research objective was to determine the direct contribution of the implementation of character education, school environment, and creative thinking to vocational competencies and to determine the indirect contribution of the implementation of character education and the school environment to creative thinking. The results showed (1) the implementation of character education directly and significantly contributed to the vocational competence of students; (2) the school environment directly and significantly contributes to the vocational competence of students; (3) creative thinking directly and significantly contributes to the vocational competence of students; (4) the implementation of character education indirectly contributes to vocational competence through creative thinking of students; and (5) the school environment does not contribute indirectly to vocational competence through students' creative thinking.